Multidimensional Evaluation of fuel performance for typical biodegradable plastics - Jiuli Ruan; Zhiyu Ma; Feilong Zhang; Kang Gao; Yuwen Guo (Energy Conversion and Management: X, 2025)
Biodegradable plastics (BPs) are prone to causing new environmental pollution because the traditional recycling and disposal systems on BPs are unclear, fuel conversion is expected to emerge as a viable treatment method. Here, the performance of four typical BPs for fuel utilization with combustion characteristics, thermogravimetric processes, as well as kinetic and thermodynamic parameters were studied. The results indicated that the calorific values of the BPs were 17.84–24.21 MJ/kg, comparable to standard coal, and their N and S contents were below 1 %. The reaction temperatures of BPs generally range from 300 to 600°C, which indicated that they were relatively easy to burn. In addition, the apparent activation energy (Eα) required for the combustion process of the BPs calculated by the FWO, KAS, and Starink methods is only 71.88–114.39 kJ/mol. The lower combustion reaction energy barrier makes BPs promising co-firing agents for substances with high combustion energy barriers. The combustion process of BPs across all stages predominantly conforms to the An model (random nucleation and nuclei growth mechanism model), with varying reaction orders observed in distinct phases. The apparent enthalpy change and Gibbs free energy change are both greater than 0, indicating that the combustion of BPs was a nonspontaneous reaction that requires the absorption of energy from the external environment. These findings are anticipated to provide critical insights for designing BP combustion reactors and establish a theoretical foundation for their fuel conversion applications.